2012
DOI: 10.1002/ijc.27799
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs in plasma as early detection markers for breast cancer

Abstract: In recent years, circulating miRNAs have attracted a great deal of attention as promising novel markers for various diseases. Here, we investigated their potential to serve as minimally invasive, early detection markers for breast cancer in blood plasma. We profiled miRNAs extracted from the plasma of early stage breast cancer patients (taken at the time-point of diagnosis) and healthy control individuals using TaqMan low-density arrays (TLDA). Selected candidates identified in the initial screen were further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
182
1
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(192 citation statements)
references
References 45 publications
6
182
1
3
Order By: Relevance
“…Moreover, previous reports described RNU6B as having unstable expression and tendency to degradation in plasma/serum samples. 18,21 Indeed, in our study, we also observed RNU6B instability in several samples. Other studies applied synthetic exogenous RNA molecules (cel-miR-39, cel-miR-54 and celmiR-238) as reference genes.…”
Section: Plasma Micrornas In Adrenocortical Tumorssupporting
confidence: 71%
See 1 more Smart Citation
“…Moreover, previous reports described RNU6B as having unstable expression and tendency to degradation in plasma/serum samples. 18,21 Indeed, in our study, we also observed RNU6B instability in several samples. Other studies applied synthetic exogenous RNA molecules (cel-miR-39, cel-miR-54 and celmiR-238) as reference genes.…”
Section: Plasma Micrornas In Adrenocortical Tumorssupporting
confidence: 71%
“…12 Recent findings have raised the potential applicability of circulating miRNAs as markers of malignancy in tumors of different organs. [20][21][22][23][24] Regarding the significant differences in tissue miRNA expression in ACTs reported in several independent studies, we hypothesized that circulating miRNAs might also be differentially expressed in benign and malignant ACTs and might serve as potential minimally invasive biomarkers of malignancy. Technical problems associated with the analysis of circulating miRNAs have also been addressed in our study.…”
mentioning
confidence: 99%
“…Furthermore, differential miRNA expression was separately examined according to the luminal B-like (HER2-positive) and HER2-positive (non luminal) subtypes. For the luminal B-like (HER2-positive) subtype, 17 miRNAs were differentially expressed (Table IV), and nine of these 17 miRNAs are reported to be correlated with breast cancer (20)(21)(22)24,(26)(27)(28)(29)(30). For the HER2-positive (non luminal) subtype, 14 miRNAs were differentially expressed (Table V), and five of these are reported to be correlated with breast cancer (17,23,25,31,32).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the nature of circulating fluids being the common reservoir for all secreted molecules from all organs and tissues, the candidate miRNA biomarker could be involved in diseases of various other organs, hence making the correlation harder. Also, higher expression of a miRNA in an affected organ is not necessarily accompanied by an increase in its plasma level, as was previously shown [66] [67]. In a related approach, instead of focusing on the disease etiology, some studies have focused on a selected panel of miRNAs, which were determined to be enriched in brain and neurons [68], thus increasing the likelihood that any changes in plasma or serum is a result of changes in neurons versus other organs.…”
Section: Resultsmentioning
confidence: 99%